Association of preoperative albumin–bilirubin with surgical textbook outcomes following laparoscopic hepatectomy for hepatocellular carcinoma - Xu, Fei-Qi; Ye, Tai-Wei; Wang, Dong-Dong; Xie, Ya-Ming; Zhang, Kang-Jun; Cheng, Jian; Xiao, Zun-Qiang; Liu, Si-Yu; Jiang, Kai; Yao, Wei-Feng; Shen, Guo-Liang; Liu, Jun-Wei; et al. (Frontiers in Oncology, 2022)
Background & Aims: Recently, the effectiveness of "Textbook outcomes (TO)" in the evaluation of surgical quality has been recognized by more and more scholars. This study tended to study the association between preoperative albumin-bilirubin (ALBI) grades and the incidence of achieving or not achieving TO (non-TO) in patients with hepatocellular carcinoma (HCC) undergoing laparoscopic hepatectomy. Methods: Patients were stratified into two groups: ALBI grade 1 (ALBI ≤ -2.60), and ALBI grade 2/3 (ALBI > -2.60). The characteristics of patients and the incidence of non-TO were compared. Multivariate analyses were performed to determine whether ALBI grade was independently associated with TO. Results: 378 patients were enrolled, including 194 patients (51.3 %) in the ALBI grade 1 group and 184 patients (48.7 %) in the ALBI grade 2/3 groups. In the whole cohort, 198 patients (52.4 %) did not achieve TO, and the incidence of non-TO in ALBI grade 2/3 groups was obviously higher than ALBI grade 1 group. (n=112, 60.9% vs. n=86, 44.3 %, P = 0.001). Multivariate analyses showed that ALBI grade 2/3 was an independent risk factor for non-TO (OR: 1.95, 95%CI 1.30-2.94, P=0.023). Conclusions: More than half (52.4%) of patients with hepatocellular carcinoma did not achieve TO after laparoscopic hepatectomy, and preoperative ALBI grade 2/3 was significantly associated with non-TO. Improving the liver function reserve of patients before operation, thereby reducing the ALBI grade, may increase the probability for patients to reach TO, and enable patients to benefit more from surgery.